The emerging neuroscience of social punishment: Meta-analytic evidence. (June 2020) - Bellucci, Gabriele; Camilleri, Julia A.; Iyengar, Vijeth; Eickhoff, Simon B.; Krueger, Frank
Highlights: Third- (TPP) and second-party (SPP) punishment share neural patterns and cognitive functions. These neural patterns and cognitive functions are, however, differently engaged by TPP and SPP. TPP loads more on brain regions associated with social cognition. SPP loads more on brain regions associated with affective processing. Functional brain network organization for TPP and SPP shows both commonalities and specificity. Abstract: Social punishment (SOP)—third-party punishment (TPP) and second-party punishment (SPP)—sanctions norm-deviant behavior. The hierarchical punishment model (HPM) posits that TPP is an extension of SPP and both recruit common processes engaging large-scale domain-general brain networks. Here, we provided meta-analytic evidence to the HPM by combining the activation likelihood estimation approach with connectivity analyses and hierarchical clustering analyses. Although both forms of SOP engaged the dorsolateral prefrontal cortex and bilateral anterior insula (AI), a functional differentiation also emerged with TPP preferentially engaging social cognitive regions (temporoparietal junction) and SPP affective regions (AI). Further, although both TPP and SPP recruit domain-general networks (salience, default-mode, and central-executive networks), some specificity in network organization was observed. By revealing differences and commonalities of the neural networks consistently activated by different types of SOP, our findings contribute to a better understanding of the neuropsychological mechanisms of social punishment behavior––one of the most peculiar human behaviors.